2021
DOI: 10.1073/pnas.2021770118
|View full text |Cite
|
Sign up to set email alerts
|

miR - 218 - 2 regulates cognitive functions in the hippocampus through complement component 3–dependent modulation of synaptic vesicle release

Abstract: microRNA-218 (miR-218) has been linked to several cognition related neurodegenerative and neuropsychiatric disorders. However, whether miR-218 plays a direct role in cognitive functions remains unknown. Here, using the miR-218 knockout (KO) mouse model and the sponge/overexpression approaches, we showed that miR-218-2 but not miR-218-1 could bidirectionally regulate the contextual and spatial memory in the mice. Furthermore, miR-218-2 deficiency induced deficits in the morphology and presynaptic neurotransmitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…The Netrin-1/DCC signaling pathway, along with the others, impacts neuronal development and synaptic plasticity [ 31 ]. MiR-218 is expressed throughout the brain, notably in the hippocampus and PFC [ 30 ]. It is expressed at various levels through life stages as seen by adolescent and adult animal models, which again implicates its role in development [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Netrin-1/DCC signaling pathway, along with the others, impacts neuronal development and synaptic plasticity [ 31 ]. MiR-218 is expressed throughout the brain, notably in the hippocampus and PFC [ 30 ]. It is expressed at various levels through life stages as seen by adolescent and adult animal models, which again implicates its role in development [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the regulation primarily happens through AMPA (α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid)-mediated excitatory transmission. Studies have shown that miR-218 abundance is regulated during hippocampal development and by chronic silencing or activation of neuronal networks [ 29 , 30 , 101 ]. Overexpression and knockdown of miR-218 demonstrated that miR-218 targets the mRNA encoding the GluA2 subunit of AMPA receptors and modulates its expression.…”
Section: Emerging Role Of Mir-218 In Disease Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to PD, AD, and ALS ( Table 1 , Table 2 and Table 3 , Figure 1 ), miR-218, has been associated with neuropsychiatric disorders and other NDs [ 135 , 249 , 267 , 268 ]. In AD it is considered a potential peripheral biomarker [ 95 ] and was shown to regulate learning and memory in a mice AD model [ 94 ] and to affect the homeostasis between phosphorylated and dephosphorylated tau proteins [ 93 ] ( Table 1 , Figure 2 ). In PD models, miR-218 plays a role in modulating the NF-κB inflammatory signaling pathway, by influencing the activity of three importins, KPNB1, KPNA3, and KPNA4 [ 107 ], and interacts with the PD related gene PRKN [ 269 ], leading to mitochondrial dysfunction through the autophagic pathway [ 188 ] ( Table 2 , Figure 2 ).…”
Section: Common Dysregulated Mirnas In Ad Pd and Alsmentioning
confidence: 99%
“…Different complement components and regulators are among the target molecules of miRNAs. For instance, miR-145, miR-150, miR-218–2, and miR-92-d negatively regulate the C3 and miR-328 induces its deposition [213] , [214] , [215] , [216] . The miR-494-3p and miR-574 also target the C7 [217] ( Fig.…”
Section: Mirnasmentioning
confidence: 99%